The Moderating Role of Operational Control in the Relationship between Entrepreneurial Activity and Innovation Performance in Car Industry of Thailand - Saroge Vasuvanich; Sudawan Somjai; Luedech Girdwichai; Vanisa Pakvichai (International Journal of Supply Chain Management, 2020)
The main focus of the current study is to investigate the moderating role of operational control in the relationship between entrepreneurial activity and innovation performance. The present research aims to observe the association between antecedents and operations control mechanism, innovation performance, and corporate entrepreneurship. Innovation performance is defined as the extent of a firms’ level of attained success in achieving technologically innovative and product market goals. A theoretical base of current study states that there is no contradiction among the operations control mechanism and corporate entrepreneurship interests. The SEM-PLS is employed as a statistical tool to analyze the data. The current data revealed that strong positive influence of risk control as moderator was found on the innovation performance and organizational boundaries relationship, and a strong negative effect on the organizations’ innovation performance and time availability relationship. Thus, the possible influence caused by operation control variables must also be acknowledged. The recent research suggested that innovation should be taken and treated by managers as a responsive process for a disciplined and structured supervision. In addition, undertaking innovative initiatives require managers to deliberately construct and understand the means of generating desirable innovation outcomes.